Strategi Komunikasi Pemasaran Akun @Mnofficialstore di Media Sosial Tiktok dalam Meningkatkan Keterdedahan Pelanggan - Euis Fauziah; Desi Hasbiyah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The development of digital technology has brought very significant changes to marketing communications. The presence of social media provides opportunities for business actors so they can market their products more effectively and efficiently. One of the social media that is currently widely used as a means of marketing communication is the TikTok platform. This platform provides many features that enable users to create and distribute content creatively so that it can reach a wider audience. This research aims to find out about the marketing communication strategies used by the @mnofficialstore account to increase customer availability. This research uses a qualitative approach with descriptive methods. Data collection techniques were carried out by means of observation, in-depth interviews and documentation of the activities of the TikTok account @mnofficialstore. Research informants consisted of account owners, buyers and people who knew the account. The results of this research show that the marketing communication strategy used by the @mnofficcialstore account is used by utilizing the TikTok platform and TikTok features such as live streaming, comment columns, hashtags and following what is currently viral. This marketing communications strategy is implemented to build relationships between audiences and account owners, increase interaction, and expand the reach of content published on the home page (FYP). Customer availability can be seen from the frequency of content viewing, as well as the intensity of interactions through comments, likes and shares. This research found inconsistencies in content upload schedules and live streaming which could be an obstacle in optimizing marketing communication strategies. Therefore, consistency in uploading video content using the TikTok platform and the features that must be used to its maximum potential is an important factor in increasing customer availability.